African sheep review: productivity and reproductive attributes indication - Tsegay Lijalem Mesele; Gebreegziabher Zereu Hadgu (Journal of Applied Animal Research)
Sheep have role in securing food in Africa. This review focused on productivity and reproductive African sheep: age at first lambing, lambing interval, litter size, birth weight, weaning weight and pre-weaning mortality of lamb were emphasized. The metadata for the review was collected through systematic approach. The reviewed finding showed that Wollo (6.1 months), Begait (11.34) and Afar (12.08) sheep breeds were the three first ranked breed type on age at first lambing while the shortest lambing interval (months) 6.60, 6.67 and 7.30 were found, respectively for Gumuz, Begait and Adilo sheep breeds. For litter size (number) Awassi X Wollo (2.08), Arsi-Bale (1.70) and Bonaga (1.36) performed better. The three larger birth weights (kg) of lamb were reported, respectively as 3.90 3.10 and 3.10 for Namaqua Afrikaner, Bepedi and Damara sheep breeds. Red massai (15.00 kg), Damara (14.10 kg) and Awassi X wollo (13.80 kg) sheep breeds had the top three larger lamb weanig weights. Regarding to pre-weaning mortality rate, Aris-Bale (13.9%), Black Head Somolia (18.3%) and Menz (19.2%) had found the lowest one. In general, the results showed that the productive and reproductive performance of African sheep breeds is low; to improve it interferences on management activities are indispensable.